Development Prospects Arowana Fish (Scleropages formosus) Cultivation Bussiness On Belonging Anderson Unedo in Desa Baru District Siak Hulu Kampar Regency of Riau Province - Asnilawati Sinambela; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in February 2016 arowana fish property Anderson Unedo in cultivation, Desa Baru Siak Hulu district at Kampar in Riau Province. It’s was aimed to determine the amount of investment and profitability, analyze the feasibility, and assess the prospects for business development arowana fish. The method used in this research is a case study. Respondents were taken in this study is the owner of cultivation and two workers Unedo Anderson. Based on the result of the research investment arowana fish property of Anderson Unedo Rp. 487.101.000, which consists of a fixed capital of Rp. 396.885 million and working capital of Rp. 90.216 million, the results of the feasibility analysis on get a profit of Rp. 93.174 million/year and RCR 1.94, FRR 19.1%, 5.2 PPC period, and prospects for the development of fish Arowana belongs Anderson Unedo quite well, views based on the criteria of investment, marketing, and fulfillment of all the subsystems of agribusiness (subsystem supply input subsystem, farming and marketing subsystems).Keyword: Prospects, Arowana, Anderson Unedo